Graphical simulation for motion platform design - Yeong Shiong, Chiew (Penerbit UTM, 2007)
The development of virtual reality (VR) technology, computer aided designs (CAD) and simulations have gained a number of interests of many researchers for the past few decades. These are effective techniques and tools to test a design product or software whereby testing in real environment is not feasible (Jo et al.). In the era where cost, time and labour effective is concerned, these techniques and tools plays a critical role in testing by allowing errors to be found in early stages. In this chapter, the development of a parallel manipulator motion platform for driving simulator is discussed. This chapter will focus on the use of simulation technology on the motion platform development. The mathematical modelling of the motion platform is developed using inverse kinematics. The motion platform mathematical model is incorporated with a VR technology (SimMechanics) for testing, validation, predictions and as well as visualization of the motion platform’s performance.